Quality of life among geriatric population: A cross-sectional study in a rural area of Sepahijala District, Tripura - Nabarun Karmakar; Anjan Datta; Kaushik Nag; Kaushik Tripura (Wolters Kluwer Medknow Publications, 2018)
Background: Quality of life (QOL) among elderly is an important area of concern which reflects the health status and well-being of this vulnerable population. Objectives: The objective of this study is to find out different domains of QOL and its association with sociodemographic factors among geriatric population. Methods: A community-based cross-sectional study was done among 76 persons aged 60 years and above from August 2016 to October 2016 in rural areas of Madhupur, Sepahijala district, Tripura. The World Health Organization QOL-BREF scale was used and analysis was done using SPSS version 20.0 statistical software. P < 0.05 was considered as statistically significant. Results: The mean QOL score was maximum in social health domain (67.32 ± 15.30), followed by environmental health (51.64 ± 10.11), lowest was in psychological domain (44.29 ± 11.50). Better physical health domain score was found among participants <70 years age. Psychological health was better among Hindu and persons from nuclear family and higher socioeconomic class, whereas male, illiterate, and businessman had better social relationship. Environmental domain score was significantly better among primary educated, businessman, and higher socioeconomic class people. Conclusion: The present study revealed social relationship domain had higher mean QOL score in comparison to other domains, but contrastingly psychological domain was affected worst in "old age group." Further research can be done to explore the factors affecting psychological domain.